If it's not what You are looking for type in the equation solver your own equation and let us solve it.
a2=26
We move all terms to the left:
a2-(26)=0
We add all the numbers together, and all the variables
a^2-26=0
a = 1; b = 0; c = -26;
Δ = b2-4ac
Δ = 02-4·1·(-26)
Δ = 104
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$a_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$a_{2}=\frac{-b+\sqrt{\Delta}}{2a}$
The end solution:
$\sqrt{\Delta}=\sqrt{104}=\sqrt{4*26}=\sqrt{4}*\sqrt{26}=2\sqrt{26}$$a_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(0)-2\sqrt{26}}{2*1}=\frac{0-2\sqrt{26}}{2} =-\frac{2\sqrt{26}}{2} =-\sqrt{26} $$a_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(0)+2\sqrt{26}}{2*1}=\frac{0+2\sqrt{26}}{2} =\frac{2\sqrt{26}}{2} =\sqrt{26} $
| x/12=3=7 | | e2=144 | | d2=24 | | c2=17 | | b2=5 | | a2=14 | | x/7=-29+40 | | e2=121 | | d2=81 | | c2=64 | | b2=169 | | x=12+8x/13 | | -2t^2-20t-30=0 | | x-9=-2+3 | | 11^-3y=2 | | x/3+x/2=7/9 | | 3x-26=-2x+54 | | 3/4p=1/5 | | x^2-2x+384=0 | | 10=(3^x+5)-2 | | -7b−7=-6b | | -6v+1=1−6v | | -6h+10h=4h | | -9+7q=6q | | 9r+9=9r | | 40,000-2x=0 | | x2=−81 | | 36w-5=1.8 | | -3^2-36t-100=0 | | -2t^2-36t-100=0 | | x=40/5 | | (s+6)(s-2)=0 |